Identification of Biomarkers for Prostate Cancer - Anna Meiliana; Andi Wijaya (The Prodia Education and Research Institute (PERI), 2014)
BACKGROUND: Prostate cancer (PCa) was the second most common type of cancer and the fifth leading cause of cancer-related death in men. The great challenge for physicians is being able to accurately predict PCa prognosis and treatment response in order to reduce PCa-specific mortality while avoiding overtreatment by identifying of when to intervene, and in which patients.CONTENT: Currently, PCa prognosis and treatment decision of PCa involved digital rectal examination, Prostate-Speciic Antigens (PSA), and subsequent biopsies for histopathological staging, known as Gleason score. However, each procedure has its shortcomings. Efforts to find a better clinically meaningful and non-invasive biomarkers still developed involving proteins, circulating tumor cells, nucleic acids, and the ‘omics' approaches.SUMMARY: Biomarkers for PCa will most likely be an assay employing multiple biomarkers in combination using protein and gene microarrays, containing markers that are differentially expressed in PCa.KEYWORDS: prostate cancer, PSA, biomarkers, nomograms, miRNA, proteomic, genomic, metabolomic